George Washington and the general's dog - Murphy, Frank; Walz, Richard (New York : Random House, 2002)
Recounts events in the life of George Washington which focus on his fondness for animals.
Keywords: Washington, George, -- 1732-1799 -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature